Exports, Foreign Direct Investment and Economic Development in China. - Fu, X (Palgrave Macmillan, 2004)
The impact of exports and FDI on the economic development of developing countries is a much-debated issue. China's membership of WTO with all the attendant rights and obligations has further fuelled the debate. Are exports an 'engine of growth' for the economy? Have exports and FDI promoted only economic growth but not development in China? What are the channels through which exports and FDI impact on economic development? This volume, based on a series analysis using up-to-date econometric technique, systematically investigates the role that exports and foreign direct investment (FDI) have played in China's development process., and questions the received wisdom that exports and FDI are always an unalloyed blessing. It focuses on the transmission mechanisms through which exports and FDI influence growth and economic development and investigates the impact of exports and FDIs on employment, development financing, productivity growth, regional income inequalities and the remarkable growth of township and village enterprises in China.